Penerapan Metode Audiolingual Melalui Pendampingan Guru Bahasa Inggris Untuk Mendukung Kurikulum Merdeka di Madrasah Ibtidaiyah NW Penyenggir - Rosyidi, Ahmad Zuhri; Lia Rismawati; M. Wahyu Hadi; Fitri Ningsi; Miftahul Huda; Muliana Hikmah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The Audiolingual Method is a language teaching approach that emphasizes habit formation through repeated practice and positive reinforcement. The main aim of this service activity is to assist and introduce teachers to the audio-lingual method which can form students' correct language habits through intensive repetition of language patterns. In practice, teaching with this method begins with listening and speaking exercises before reading and writing. Applying this method requires students to memorize dialogue, imitate intonation and pronunciation correctly, and respond automatically to verbal stimuli. Correction of errors is carried out directly to prevent the formation of wrong habits. The use of the mother tongue is minimized, even avoided, so that students get used to thinking in English. The result of this activity is that the teachers are very enthusiastic in learning and applying the audiolingual method. Moreover, this activity is strengthened by participants and practical application directly to students. Overall, the Audiolingual method is effective in the early stages of language learning, especially to build basic oral skills. However, it needs to be combined with other approaches so that language mastery becomes more balanced and communicative.